Decision support systems X : cognitive decision support systems and technologies : 6th International Conference on Decision Support System Technology, ICDSST 2020, Zaragoza, Spain, May 27-29, 2020, proceedings /: cognitive decision support systems and technologies : 6th International Conference on Decision Support System Technology, ICDSST 2020, Zaragoza, Spain, May 27-29, 2020, proceedings. (2020) - Unknown
No abstract available